Authentic assessment in Indonesian in elementary schools: a framework on language teaching - Muzaki, Ferril Irham (2022)
The learning process, the characteristics of an adequate learning process are needed,which accommodate aspirations that adjust to the characteristics of the student himself. In the design of the learning process design, it is necessary to change the circumstances that accompany it. Portfolio-based assessment is an integral part of the design of the design and governance systems encountered in schools. Providing opportunities for designing design and governance, a design pattern is needed that provides opportunities for students to determine their destinies and adequate systems of thought, besides adequate skills for designing designs and steps in the learning process. Learning process, a process and effort are needed in designing characteristics to design actualization in terms of designing adequate capabilities. This is the starting point of the achievement of a design that provides opportunities for the creation of adequate devices. The use of logic in everyday life cannot be separated from the use of transformation and adequate design. Planning for an assessment design even though it is accompanied by the creation of an actual design of engineering. In this case, to plan a design, although accompanied by a performance survey and the utilization of the work done in the field, it is then poured into an adequate design. In terms of design utilization of assessment, a pupil even learns about how to design an actual design follows the contours of the times' that allow a student to make the optimal design, which is now becoming an integral ingredient in designing an authentic design.